Pengaruh Model Pembelajaran Berbasis Proyek terhadap Kreativitas Anak Usia 5-6 Tahun di Taman Kanak-Kanak Panrannuangku 1 - Rini Afriani Darmayanti; Parwoto; Azizah Amal (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This study aims to determine the effect of project-based learning models on the creativity of children aged 5-6 years at Panrannuangku Kindergarten 1. This research was conducted using a quantitative approach with a quasi-experiment design. The population amounted to 36 students at Panrannuangku 1 Kindergarten. In this study, the sample was taken randomly from 12 children, each 6 children in the experimental group and 6 children in the control group. Descriptive and non-parametric statistical analysis was used to collect data. In this study, the results obtained Thitung 71 > Ttabel 2.2281 = H0 is rejected and H1 is accepted, meaning that there is an effect of project-based learning models on children's creativity. The value of Zhitung 1.52 > Ztabel 0.4394 = H0 is rejected and H1 is accepted, meaning that there is an effect of project-based learning models on children's creativity. So it can be concluded that creativity in the experimental class is better than the control class, this proves that the project-based learning model using origami influences children's creativity.